TEKNIKALISASI PEMETAAN WILAYAH ADAT: KETAHANAN SOSIAL BUDAYA ORANG SUMURI DI KABUPATEN TELUK BINTUNI, PROVINSI PAPUA BARAT - Suryawan, I Ngurah (Masyarakat Indonesia, 2018)
This article aims to analyze the impacts of increasing bussiness investment in Sumuri District, Bintuni Bay, West Papua Province. One of the company social responsbility (CSR) is mapping the customary rights to identify some areas that would become business’s location. As the results, it appears the complexity issues that connect social and cultural resistance to the technicalization of mapping problems. Territorialising indigenous community’s territories happens and they were trapped in the processes of regulation prepared by the local government and investors. The most difficult challenge is to clear up the process of mapping technicalization that has become into the state and investor perpsectives. Therefore, this article attempts to explore social processes in negotiations between technicalization ofclan territories and expectations of local communities on sociocultural changes. In this contestation, imagination about the customs and cultures involved in the current sociocultural changes and the setting becomes very problematic and risky. So, this article is necessary to find out which social and cultural resilience are the local communities expect.